Teleconnected ocean forcing of Western North American droughts and pluvials during the last millennium. (15th August 2016) - Routson, Cody C.; Woodhouse, Connie A.; Overpeck, Jonathan T.; Betancourt, Julio L.; McKay, Nicholas P.
Abstract: Western North America (WNA) is rich in hydroclimate reconstructions, yet questions remain about the causes of decadal-to-multidecadal hydroclimate variability. Teleconnection patterns preserved in annually-resolved tree-ring reconstructed drought maps, and anomalies in a global network of proxy sea surface temperature (SST) reconstructions, were used to reassess the evidence linking ocean forcing to WNA hydroclimate variability over the past millennium. Potential forcing mechanisms of the Medieval Climate Anomaly (MCA) and individual drought and pluvial events—including two multidecadal-length MCA pluvials—were evaluated. We show strong teleconnection patterns occurred during the driest (wettest) years within persistent droughts (pluvials), implicating SSTs as a potent hydroclimate forcing mechanism. The role of the SSTs on longer timescales is more complex. Pacific teleconnection patterns show little long-term change, whereas low-resolution SST reconstructions vary over decades to centuries. While weaker than the tropical Pacific teleconnections, North Atlantic teleconnection patterns and SST reconstructions also show links to WNA droughts and pluvials, and may in part account for longer-term WNA hydroclimate changes. Nonetheless, evidence linking WNA hydroclimate to SSTs still remains sparse and nuanced—especially over long-timescales with a broader range of hydroclimatic variability than characterized during the 20th century. Highlights: Both Pacific and, to a lesser extent, Atlantic SSTs likely influenced Western droughts and pluvials. Anomalous years within prolonged events exhibit the strongest teleconnections. Two Medieval Period pluvials likely had different causal mechanisms.